Born to exile - Eisenstein, Phyllis, 1946- (Arkham House science fiction novel, 1978)
The solitary wanderings of a minstrel with preternatural powers lead him to many adventures before he is ultimately restored to his supernatural antecedents, the Lords of All Power.